Causal Factors Affecting Purchase Intention of Movies Watch on Disney Plus Hotstar Application in Thailand - Pankham, Sumaman; Kalwantawanit, Saruta (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this research article were 1) to develop and validate the consistency of a causal relationship model of purchase intention of movies watched on the Disney Plus Hotstar application in Thailand and 2) to study causal factors affecting purchase intention of movies watched on the Disney Plus Hotstar application in Thailand. The sample group consisted of 400 people who had the purchase intention of watching movies on the Disney Plus Hotstar application in Thailand. The tools used in the research were online questionnaires. The statistics used in data analysis were frequency, percentage, and the structural equation model. The results of this research were the development of causal relationship models consisting of 5 components, which were 1) corporate social responsibility (CSR), 2) trust, 3) brand image, 4) awareness, and 5) purchase intention and a model developed in accordance with empirical data. The statistics showed the Chi-square statistics goodness fit test (χ2) = 188.81, degrees of freedom (df) 138, CMIN/df = 1.37, GFI = 0.96, AGFI = 0.92, SRMR = 0.02, RMSEA = 0.03. The final result was a predictive coefficient of 0.64, indicating that the variables in the model can explain the purchase intention of movies watched on the Disney Plus Hotstar application of consumers in Thailand by 64% and that trust, awareness, and brand image influence the purchase intention of movies watched on the Disney Plus Hotstar application in Thailand.